Potential Tourism Market in Transition Countries: A Regional Analysis - Eva Aguayo; Pilar Exposito; Emilia Vazquez (European Regional Science Association (ERSA), 2006)
Tourism is a very important sector for the economic growth and the employment. It is also important to stress that this relationships have not been studied enough, this is even more important if we take into account that we consider the economic impact, not the major determinants of tourist demand, which is the most common feature of tourism studies. In this paper we analyse the economic impact of tourism in the economy of 50 regions of transition countries. The political and economic changes in these countries have brought the attention in this area, making it a desirable destination for an important part of tourists, both in Europe and other parts of the world. Nowadays tourist are not seeking just sun and beaches as it happened in the past, other factors such as culture, history, archaeology or natural parks can explain some of the changes in the movement of tourists around the world. We study the difference among the countries and regions, considering the importance of resident and non-residents tourism in each of them. Through this analysis we would like to point those countries, and regions, which are already in a good position, such as the Czech Republic, Hungary or Poland, comparing them with those others which offer an important potential to develop this sector.
Keywords: 330